The biosynthetic gene cluster for sophorolipids: a biotechnological interesting biosurfactant produced by Starmerella bombicola. Issue 3 (21st March 2013) - Van Bogaert, Inge N. A.; Holvoet, Kevin; Roelants, Sophie L. K. W.; Li, Bing; Lin, Yao‐Cheng; Van de Peer, Yves; Soetaert, Wim
Summary Sophorolipids are promising biological derived surfactants or detergents which find application in household cleaning, personal care and cosmetics. They are produced by specific yeast species and among those, Starmerella bombicola (former Candida bombicola) is the most widely used and studied one. Despite the commercial interest in sophorolipids, the biosynthetic pathway of these secondary metabolites remained hitherto partially unsolved. In this manuscript we present the sophorolipid gene cluster consisting of five genes directly involved in sophorolipid synthesis: a cytochrome P450 monooxygenase, two glucosyltransferases, an acetyltransferase and a transporter. It was demonstrated that disabling the first step of the pathway – cytochrome P450 monooxygenase mediated terminal or subterminal hydroxylation of a common fatty acid – results in complete abolishment of sophorolipid production. This phenotype could be complemented by supplying the yeast with hydroxylated fatty acids. On the other hand, knocking out the transporter gene yields mutants still able to secrete sophorolipids, though only at levels of 10% as compared with the wild type, suggesting alternative routes for secretion. Finally, it was proved that hampering sophorolipid production does not affect cell growth or cell viability in laboratory conditions, as can be expected for secondary metabolites.